Research on Performance Evaluation Index of Dew Point Evaporative Cooler - L; Jing; Huang Jiahao; Xu Haodong; Xu Tangfuyi (Zhileng xuebao)
According to experiments performed on a counter flow dew point evaporative cooling device, the effects of the air inlet temperature, humidity, and air speed on the dew point efficiency, wet bulb efficiency, exergy efficiency ratio, and other performance evaluation indicators were analyzed in this study. The proposed heat transfer amplification coefficient is suitable for dew point evaporative cooling, which can reflect the strength of latent heat exchange in the wet channel and the performance of the device. The research results indicate that when the inlet temperature is 33 ℃ and the relative humidity is 22%, the air speed increases from 1 m/s to 3 m/s, the refrigeration capacity increases from 29.5 kW to 69.0 kW, and the heat transfer amplification coefficient first increases and then decreases, reaching the maximum value at an air speed of 1.8 m/s. In addition, the change law of the wet-bulb efficiency and the dew point efficiency is inconsistent with the temperature drop trend and refrigeration effect. Therefore, both wet-bulb efficiency and dew point efficiency are unsuitable as a performance evaluation index of the device. When the relative humidity is 43% and the air speed is 1.3 m/s, the inlet temperature increases from 25 °C to 40 °C, and the heat transfer amplification factor increases from 11 to 54. The change is consistent with the cooling effect, which can reflect the cooling performance of the device. The exergy efficiency ratio can be used to evaluate the energy saving of this device from the perspective of thermodynamics. Under high temperature and low humidity conditions, the exergy efficiency ratio is larger, and the device is more energy-saving.